Soil Water Index Dynamics for the Identification of Initial Occurrence of Volcanic Deposit Instability - Wardoyo, Wasis; Legono, Djoko; Jayadi, Rachmad; Fathani, Teuku Faisal (2011)
Several techniques have been introduced in order to monitor important parameters of disaster symptoms, and then utilizing them to develop necessary warning criteria. In case of Mt. Merapi disaster, where after the 2010 eruption the intensity of lahar flow occurrence increases significantly, such monitoring system is becoming very important. This is due to the fact that activity at the surrounding volcanic rivers is very intensive, in the form of both settlement at the surrounding rivers and the sediment mining activity in the rivers itself. Furthermore, in almost all cases of the development of early warning system, minimizing number of casualties or toll death has become main target. This paper presents the results of investigation on lahar flow warning criteria development through soil moisture monitoring activity at Gendol River of Mt. Merapi, before and after 2010 eruption confronted with some laboratory investigation. Correlation between the soil moisture dynamics and the initial occurance of volcanic deposit instability are then presented. Analysis from relatively reliable data performs the goodness fit of the correlation between the aforesaid parameters .